A Real-World Study of Switching From Allopurinol to Febuxostat in a Health Plan Database. Issue 8 (December 2015) - Altan, Aylin; Shiozawa, Aki; Bancroft, Tim; Singh, Jasvinder A.
Abstract : Objective: The objective of this study was to assess the real-world comparative effectiveness of continuing on allopurinol versus switching to febuxostat. Methods: In a retrospective claims data study of enrollees in health plans affiliated with Optum, we evaluated patients from February 1, 2009, to May 31, 2012, with a gout diagnosis, a pharmacy claim for allopurinol or febuxostat, and at least 1 serum uric acid (SUA) result available during the follow-up period. Univariate and multivariable-adjusted analyses (controlling for patient demographics and clinical factors) assessed the likelihood of SUA lowering and achievement of target SUA of less than 6.0 mg/dL or less than 5.0 mg/dL in allopurinol continuers versus febuxostat switchers. Results: The final study population included 748 subjects who switched to febuxostat from allopurinol and 4795 continuing users of allopurinol. The most common doses of allopurinol were 300 mg/d or less in 95% of allopurinol continuers and 93% of febuxostat switchers (prior to switching); the most common dose of febuxostat was 40 mg/d, in 77% of febuxostat switchers (after switching). Compared with allopurinol continuers, febuxostat switchers had greater (1) mean preindex SUA, 8.0 mg/dL versus 6.6 mg/dL ( P < 0.001); (2) likelihood of postindex SUA of less than 6.0 mg/dL, 62.2% versus 58.7% ( P = 0.072); (3) likelihood of postindex SUA of less than 5.0 mg/dL, 38.9% versus 29.6% ( P < 0.001); and (4) decrease in SUA, 1.8 (SD, 2.2) mg/dL versus 0.4 (SD, 1.7) mg/dL ( P < 0.001). In multivariable-adjusted analyses, compared with allopurinol continuers, febuxostat switchers had significantly higher likelihood of achieving SUA of less than 6.0 mg/dL (40% higher) and SUA of less than 5.0 mg/dL (83% higher). Conclusions: In this "real-world" setting, many patients with gout not surprisingly were not treated with maximum permitted doses of allopurinol. Patients switched to febuxostat were more likely to achieve target SUA levels than those who continued on generally stable doses of allopurinol. Abstract : Supplemental digital content is available in the text.